Manevi Zararın Belirlenmesi ve Manevi Tazminatın Hesaplanması - Türk Hukukuna Manevi Zararın İki Aşamalı Olarak Belirlenmesine İlişkin Bir Model Önerisi - (:unkn) unknown (My University, 2016)
Çalışmada, uygun bir miktar paranın manevi tazminat olarak belirlenmesi üzerinde durulmuş, konuya ilişkin hakimin takdir yetkisi de incelenmiştir. Konu, İsviçre Federal Mahkemesi'nin ve Yargıtay'ın uygulamaları ile birlikte karşılaştırmalı olarak ele alınarak, manevi tazminatın belirlenmesine ilişkin Yargıtay uygulamasındaki aksaklıklara değinilmiştir.

In this article, determination of sufficient amount of money as a moral damage and judicial discretion concerning to the subject matter are addressed. This subject matter is examined in the light of Switzerland Bundesgericht and the Supreme Court of Appeal's enforcements. Furthermore, deficiencies of Supreme Court of Appeal's decisions in the determination of moral damage are analyzed.
Determination of Moral Damages and Evaluation of Damages For Pain and Suffering Proposal for the Evaluation of Moral Damages in Two Stages in Turkish Law
Keywords: Hukuk